The investigation of measurement method for HPM radiation to the analog switch chip - Minkyun Yoo; Wonkyu Kim; Yoon-Mi Park; Min-Hyuk Kim; Young-Seek Chung; Hyun-Kyo Jung; Changyul Cheon (2010 IEEE International Symposium on Electromagnetic Compatibility, 2010)
In this paper we suggest a special measurement system using an optical transformation when an analog switch chip is exposed by an external High Power Microwave(HPM). The proposed measurement system can compare a normal operation with a malfunction of the chip, analyzed signals at each pin of the chip when the HPM radiates to the chip. To analyze accurately the operation of the chip proposed measurement system uses an optical communication method. An electrical signal of the chip is modulated to an optical signal by a laser diode(LD) within the range of the HPM. After that, the modulated optical signal is demodulated to the electrical signal by a photo diode(PD) beyond the range of the HPM and then signal is measured. Because this system has no interference between frequency of microwaves and optical waves, an accurate analysis is possible.